Triple-channel microreactor for biphasic gas–liquid reactions: Photosensitized oxygenations - Maurya, Ram Awatar; Park, Chan Pil; Kim, Dong-Pyo (Beilstein Journal of Organic Chemistry, 2011)
A triple-channel microreactor fabricated by means of a soft-lithography technique was devised for efficient biphasic gas–liquid reactions. The excellent performance of the microreactor was demonstrated by carrying out photosensitized oxygenations of α-terpinene, citronellol, and allyl alcohols.
Keywords: gas–liquid reaction; microreactor; photosensitization; singlet oxygen

(untitled) - Whitesides, G. M. (Nature, 2006)

(untitled) - Hartman, R. L.; Jensen, K. F. (Lab Chip, 2009)

(untitled) - Tanaka, K.; Fukase, K. (Beilstein J. Org. Chem., 2009)

(untitled) - Wiles, C.; Watts, P.; Haswell, S. J. (Lab Chip, 2007)

(untitled) - Zhao, C.-X.; He, L.; Qiao, S. Z.; Middelberg, A. P. J. (Chem. Eng. Sci., 2011)

(untitled) - Hornung, C. H.; Mackley, M. R.; Baxendale, I. R.; Ley, S. V. (Org. Process Res. Dev., 2007)

(untitled) - Kobayashi, J.; Mori, Y.; Okamoto, K.; Akiyama, R.; Ueno, M.; Kitamori, T.; Kobayashi, S. (Science, 2004)

(untitled) - Wiles, C.; Watts, P. (Adv. Chem. Eng., 2010)

(untitled) - Wang, N.; Matsumoto, T.; Ueno, M.; Miyamura, H.; Kobayashi, S. (Angew. Chem., Int. Ed., 2009)

(untitled) - Miller, P. W.; Long, N. J.; de Mello, A. J.; Vilar, R.; Audrain, H.; Bender, D.; Passchier, J.; Gee, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Mak, X. Y.; Laurino, P.; Seeberger, P. H. (Beilstein J. Org. Chem., 2009)

(untitled) - Rahman, M. T.; Fukuyama, T.; Kamata, N.; Sato, M.; Ryu, I. (Chem. Commun., 2006)

(untitled) - Rebrov, E. V.; Klinger, E. A.; Berenguer-Murcia, A.; Sulman, E. M.; Schouten, J. C. (Org. Process Res. Dev., 2009)

(untitled) - Lemke, E. A.; Gambin, Y.; Vandelinder, V.; Brustad, E. M.; Liu, H.-W.; Schultz, P. G.; Groisman, A.; Deniz, A. A. (J. Am. Chem. Soc., 2009)

(untitled) - Aota, A.; Nonaka, M.; Hibara, A.; Kitamori, T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Razzaq, T.; Kappe, C. O. (Chem.–Asian J., 2010)

(untitled) - Park, C. P.; Van Wingerden, M. M.; Han, S.-Y.; Kim, D.-P.; Grubbs, R. H. (Org. Lett., 2011)

(untitled) - Park, C. P.; Kim, D.-P. (Angew. Chem., Int. Ed., 2010)

(untitled) - Rasheed, M.; Wirth, T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Brivio, M.; Verboom, W.; Reinhoudt, D. N. (Lab Chip, 2006)

(untitled) - Mason, B. P.; Price, K. E.; Steinbacher, J. L.; Bogdan, A. R.; McQuade, D. T. (Chem. Rev., 2007)

(untitled) - He, P.; Watts, P.; Marken, F.; Haswell, S. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Nagaki, A.; Takabayashi, N.; Tomida, Y.; Yoshida, J.-i. (Beilstein J. Org. Chem., 2009)

(untitled) - Tomida, Y.; Nagaki, A.; Yoshida, J.-i. (J. Am. Chem. Soc., 2011)

(untitled) - Frost, C. G.; Mutton, L. (Green Chem., 2010)

(untitled) - Mennecke, K.; Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Shore, G.; Tsimerman, M.; Organ, M. G. (Beilstein J. Org. Chem., 2009)

(untitled) - Massi, A.; Cavazzini, A.; Del Zoppo, L.; Pandoli, O.; Costa, V.; Pasti, L.; Giovannini, P. P. (Tetrahedron Lett., 2011)

(untitled) - Tricotet, T.; O'Shea, D. F. (Chem.–Eur. J., 2010)

(untitled) - Bogdan, A. R.; Poe, S. L.; Kubis, D. C.; Broadwater, S. J.; McQuade, D. T. (Angew. Chem., Int. Ed., 2009)

(untitled) - Palde, P. B.; Jamison, T. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Brandt, J. C.; Wirth, T. (Beilstein J. Org. Chem., 2009)

(untitled) - Gutmann, B.; Roduit, J.-P.; Roberge, D.; Kappe, C. O. (Angew. Chem., Int. Ed., 2010)

(untitled) - Carofiglio, T.; Donnola, P.; Maggini, M.; Rossetto, M.; Rossi, E. (Adv. Synth. Catal., 2008)

(untitled) - Meyer, S.; Tietze, D.; Rau, S.; Schäfer, B.; Kreisel, G. (J. Photochem. Photobiol., A: Chem., 2007)

(untitled) - Jähnisch, K.; Dingerdissen, U. (Chem. Eng. Technol., 2005)

(untitled) - Bourne, R. A.; Han, X.; Poliakoff, M.; George, M. W. (Angew. Chem., Int. Ed., 2009)

(untitled) - Wootton, R. C. R.; Fortt, R.; de Mello, A. J. (Org. Process Res. Dev., 2002)

(untitled) - O'Brien, M.; Taylor, N.; Polyzos, A.; Baxendale, I. R.; Ley, S. V. (Chem. Sci., 2011)

(untitled) - Polyzos, A.; O’Brien, M.; Petersen, T. P.; Baxendale, I. R.; Ley, S. V. (Angew. Chem., Int. Ed., 2011)

(untitled) - Chambers, R. D.; Holling, D.; Spink, R. C. H.; Sandford, G. (Lab Chip, 2001)

(untitled) - Chambers, R. D.; Fox, M. A.; Holling, D.; Nakano, T.; Okazoe, T.; Sandford, G. (Lab Chip, 2005)

(untitled) - Park, C. P.; Kim, D.-P. (J. Am. Chem. Soc., 2010)

(untitled) - Park, C. P.; Maurya, R. A.; Lee, J. H.; Kim, D.-P. (Lab Chip, 2011)

(untitled) - Lee, J. N.; Park, C.; Whitesides, G. M. (Anal. Chem., 2003)

(untitled) - Monnerie, N.; Ortner, J. J. (Sol. Energy Eng., 2001)

(untitled) - Griesbeck, A. G.; El-Idreesy, T. T.; Lex, J. (Tetrahedron, 2006)

(untitled) - Bezerra, D. P.; Marinho Filho, J. D. B.; Alves, A. P. N. N.; Pessoa, C.; de Moraes, M. O.; Pessoa, O. D. L.; Torres, M. C. M.; Silveira, E. R.; Viana, F. A.; Costa-Lotufo, L. V. (Chem. Biodiversity, 2009)